Nurse Practitioners and Physician Assistants: An Underestimated Workforce for Older Adults with Cancer. Issue 7 (6th May 2019) - Coombs, Lorinda A.; Max, Wendy; Kolevska, Tatjana; Tonner, Chris; Stephens, Caroline
Abstract : OBJECTIVES: To describe the composition of the US provider workforce for adults with cancer older than 65 years and to determine whether there were differences in patients who received care from different providers (eg, nurse practitioners [NPs], physician assistants [PAs], and specialty physicians). DESIGN: Observational, cross‐sectional study. SETTING: Adults within the 2013 Surveillance, Epidemiology, and End Results cancer registries linked to the Medicare claims database. PARTICIPANTS: Medicare beneficiaries who received ambulatory care for any solid or hematologic malignancies. MEASUREMENTS: International Classification of Diseases, Ninth Revision ( ICD‐9 ), diagnosis codes were used to identify Medicare patient claims for malignancies in older adults. Providers for those ambulatory claims were identified using taxonomy codes associated with their National Provider Identifier number. RESULTS: A total of 2.5 million malignancy claims were identified for 201, 237 patients, with 15, 227 providers linked to claims. NPs comprised the largest group (31.5%; n = 4, 806), followed by hematology/oncology physicians (27.7%; n = 4, 222), PAs (24.7%; n = 3767), medical oncologists (10.9%; n = 661), gynecological oncologists (2.6%; n = 403), and hematologists (2.4%; n = 368). Rural cancer patients were more likely to receive care from NPs (odds ratio [OR] = 1.84; 95% confidence interval [CI] = 1.65‐2.05) or PAs (OR = 1.57; 95% CI = 1.40‐1.77) than from physicians. Patients in the South were more likely to receive care from NPs (OR = 1.36; 95% CI = 1.24‐1.49). CONCLUSIONS: A large proportion of older adults with cancer receive care from NPs and PAs, particularly those who reside in rural settings and in the southern United States. Workforce strategies need to integrate these provider groups to effectively respond to the rising need for cancer care within the older adult population.